Inhibitors targeting the autophosphorylation of serine/threonine kinase of Streptococcus suis show potent antimicrobial activity - Li, Haotian; Li, Tingting; Hu, Qiao; Yao, Zhiming; Li, Lu; Huang, Qi; Zhou, Rui (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) is a global concern threatening public health. Developing novel antibiotics is one of the effective strategies to tackle AMR. Serine/threonine kinases (STKs) have been recently shown to play critical roles in the physiology and pathogenesis of several important bacterial pathogens which are regarded as a promising antimicrobial drug target. We previously reported the roles of STK in the regulation of bacterial cell division, metabolism, and pathogenesis in Streptococcus suis, an important zoonotic bacterial pathogen. In this study, we firstly identified the Thr167 and Ser175 residues in the activation loop of S. suis STK (ssSTK) as the kinase autophosphorylation sites. Phenotyping results demonstrated that the autophosphorylation deficient strain resembled the stk deletion strain showing essentiality for bacterial growth in minimal medium, abnormal morphology, and decreased virulence when compared with the wild-type S. suis SC19 strain. Based on these findings, we established an ssSTK inhibitor screening approach by measuring the growth of S. suis in a minimal medium and testing the autophosphorylation inhibition by measuring the consumption of ATP in an enzymatic reaction by ssSTK. A series of inhibitors against ssSTK are identified from a commercial kinase inhibitors library, including Staurosporine, K252a, AT9283, and APY29. These inhibitors showed antimicrobial activity in vitro. Moreover, by using Galleria mellonella larvae infection assay, compound APY29 displayed in vivo efficacy against S. suis infection. Additionally, it was predicted by molecular docking that these inhibitors could interact with ssSTK. Collectively, our data illustrated the essential roles of ssSTK autophosphorylation in the physiology and pathogenicity of S. suis and consider these inhibitors as promising antimicrobial lead compounds.